2013
DOI: 10.28945/1891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Screencasting on the Turkish Undergraduate Students’ Achievement and Knowledge Acquisitions in Spreadsheet Applications

Abstract: Executive SummaryThe purpose of this study is to investigate the effects of screencasts on the Turkish undergraduate students' achievement and knowledge acquisitions in spreadsheet applications. The methodology of the study is based on a pretest-posttest experimental design with a control group. A total of 66 undergraduate students in two groups (n=33 in experimental, and n= 33 in control) participated both in the multiple choice and practical pretests and posttests. There was no significant difference between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…With high-end screencasting software, the creator has the ability to remove extraneous portions of the video and add audio postrecording to create a concise, attractive learning experience. In a Turkish study of undergraduate students learning spreadsheet applications, the use of screencasts positively affected not only comprehension and knowledge of concepts, but also achievement and performance of learned skills (Tekinarslan, 2013). In another study, Green et al (2012) report that students had a favorable perception towards screencasting, and attributed their improvements in course performance to screencast availability.…”
Section: Screencastsmentioning
confidence: 97%
“…With high-end screencasting software, the creator has the ability to remove extraneous portions of the video and add audio postrecording to create a concise, attractive learning experience. In a Turkish study of undergraduate students learning spreadsheet applications, the use of screencasts positively affected not only comprehension and knowledge of concepts, but also achievement and performance of learned skills (Tekinarslan, 2013). In another study, Green et al (2012) report that students had a favorable perception towards screencasting, and attributed their improvements in course performance to screencast availability.…”
Section: Screencastsmentioning
confidence: 97%
“…Most of the screencasts were used for formative feedback, but those who use screencasting for summative feedback indicated that the feedback was more likely to be considered than written feedback alone (Cranny 2016;Tekinarslan 2013). All studies reported an increased likelihood of uptake by the students.…”
Section: Studies Of Feedback Given Through Screencastingmentioning
confidence: 99%
“…Screencasting allows instructors to record an activity on a computer screen and simultaneously capture the audio explanation and then place the finished recording, often augmented with visual captions, on a website for distribution and access (Morris & Chikwa, 2014). Since the technology first become available, screencasts have been widely used for teaching a variety of topics and subjects, such as student research, assistive technologies, nursing, programming, instructional design, (Sugar et al, 2010), database applications (Tekinarslan, 2013), anatomy (Pickering, 2017), referencing skills (Stagg et al, 2013) and statistics (Lloyd & Robertson, 2012). Screencasts are notably useful in demonstrating step-by-step instructions for specific software programs or activities that involve a sequence of steps (Peterson, 2007).…”
Section: Screencastsmentioning
confidence: 99%